Public contestation over agricultural pollution: a discourse network analysis on narrative strategies in the policy process - Bulian, Simon (Policy sciences, 2021)
The overuse of fertilizers in agriculture and their entry into freshwater has many negative impacts on biodiversity and poses problems for drinking water resources in Germany. In response to exceeding levels of nitrate concentrations in groundwater in parts of the country, an intense public dispute evolved and a significant policy change in fertilizer regulation occurred in 2020. Based on the German case of agricultural water pollution, this study demonstrates in an innovative way how discourse network analysis is a fruitful method for the integrated study of actor coalitions and their use of narrative strategies in public debate. Theoretically, the study draws on the narrative policy framework (NPF) to explain how actor coalitions use narrative strategies to attempt to influence policymaking on water pollution by agricultural activities. The empirical analysis builds on newspaper articles and press releases disseminated between 2010 and 2020. The results demonstrate how two opposing actor coalitions with congruent policy beliefs formed in the struggle over fertilizer regulation. These not only diverged in their policy beliefs but also differed in their use of narrative strategies to try to expand or contain the policy issue. More precisely, the coalitions adapted their narratives over time in response to changes in the likelihood to win or lose. Furthermore, the results suggest the coalition in favor of stricter fertilizer regulation was more sophisticated in its effort to mobilize specific target groups. Overall, the article provides a valuable contribution to the literature on the NPF by combining research on coalition formation and policy narratives.
Gesehen am 01.09.2023